Change in exposure of children to second-hand smoke with impact on children's health and change in parental smoking habits after smoking ban in Bavaria - a multiple cross-sectional study - Mohammed El Sharkawy; Stefanie Heinze; Lana Hendrowarsito; Alisa Weinberger; Jonas Huß; Uta Nennstiel; Caroline Herr; Susanne Kutzora; for the GME Study Group (BMC, 2021)
Abstract Background Concerns about smoking displacement from public places to private amenities aroused following smoking ban implementation in Bavaria in 2008. We analysed children's exposure to second-hand smoke (SHS) before and after the ban, its effect on children's health and prevalence of active smoking in adults. Methods Six cross-sectional surveys (n = 32,443) on pre-school children in Bavaria were analysed, two surveys before the smoking ban in years 2004 and 2005 (S1 and S2) and four after the ban in 2008, 2012, 2014 and 2016 (S4, S6, S7 and S8). Using multivariable logistic regression, we analysed change in children's intra- and extrauterine SHS exposure and its adverse health effects (Asthma, wheezing, bronchitis and neurodermatitis) as well as change in parental active smoking. Results The response rates were 78% for S1, 73% for S2, 61% for S4, 62% for S6, 56% for S7 and 54% for S8. Odds of parents never smoked at home in presence of children increased significantly from before to after the ban with odds ratios (OR) 1.17 (CI95% 1.01-1.35), 1.65 (CI95% 1.39-1.95), 2.85 (CI95% 2.32-3.51), 2.24 (CI95% 1.84-2.72) and 3.66 (CI95% 2.89-4.63) for S2, S4, S6, S7 and S8, respectively with S1 as reference. Compared to S4, odds of parents who were not actively smoking is significantly higher in S7 (OR = 1.13 (CI95% 1.03-1.24)) and S8 (OR = 1.24 (CI95% 1.13-1.36)). The odds of mothers who never smoked during pregnancy increased over time with OR = 1.22 (CI95% 1.06-1.40) for S2 and 1.57 (CI95% 1.33-1.86) for S8 compared to S1. Adverse health effects related to children's exposure to SHS are significantly less in S8 compared to S1. Conclusion After 11 years of smoking ban in Bavaria, smoking displacement to homes was disproved. Exposure of children to SHS intrauterine and at home is decreasing. Number of parents who are not actively smoking is increasing over time. Prevalence of health problems in children related to exposure to SHS is decreasing.